The human placenta as a model for training and research in mechanical thrombectomy: Clarifications and use of the chorionic plate veins - Burel, Julien; Cornacchini, Jonathan; Garnier, Matthieu; Patrier, Sophie; Guigné, Albane; Gerardin, Emmanuel; Papagiannaki, Chrysanthi; Sourour, Nader; Shotar, Eimad; Premat, Kévin; Laporte, Claire; Clarençon, Frédéric (Frontiers in Neurology, 2022)
Indications for mechanical thrombectomy in acute ischemic stroke are increasing, resulting in the continuous development of new devices and techniques. Therefore, there is a need for a realistic testing and training environment that offers the opportunity to practice different procedures and test the latest devices. Some authors have described the use of the human placenta as a model for neurointerventional surgery, with striking similarities to real-life conditions. This model has many advantages, including its relatively low cost and minimal infrastructure requirements, with fewer ethical concerns compared to animal models. So far, some preparation and set-up details were missing, and only arteries from the chorionic plate were used. This article provides the necessary clarifications and a mapping of the chorionic plate veins, so that the use of this model, which is particularly well suited for mechanical thrombectomy, can be as easy and wide as possible. A video explaining how to prepare the model is provided.